O pochodzeniu pomorskich grobowców bezkomorowych kultury pucharów lejkowatych - Jankowska, Dobrochna (Wydawnictwo Naukowe UAM, 2005)
The article presents a short overview of discussion on the origin of the Funnel Beaker Culture in particular regions of Pomerania. In particular, an origin of the Pomerania long barrows with a stone construction is debated. The study implies that prototypes o f these monuments are to be found in the Lower Elbe region and influences from Kujavia are only detectable in the latest phase. The article tackles also a theory linking an emergence of long barrows with the late Danubian tradition („long houses”).
On the origin of the Pomerania long barrows of the Funnel Beaker Culture